Pengaruh Sistem Pengendalian Internal Pemerintah Desa, Kompetensi Sumber Daya Manusia, dan Efektivitas Sistem Keuangan Desa Terhadap Penerapan Good Village Governance - Ni Wayan Desi Sawitri; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2020)
This research aims to determine the effect to the village government’s internal control system, human resource competencies and the effecttiveness of the village financial systemnon the implementation of good village governance in villages in Buleleng Regency. The type of the research is quantitative research. The populatian in thid research is all villages in Buleleng Regency, namely 129 villages. Sampling in this research used probability sampling techniques using a sample of 56 villages and 168 respondents. In this research data were obtained through a questionnaire distributed directly to respondents. Data analysis in this research uses multiple linear regression analysis with the help of SPSS version 20.0. The results this research stated that the internal control system of villages government, human resource competency, and effectiveness of the village financial system had a positive and significant effect on the implementation of good village governance.